Development of an upper limb rehabilitation system using inertial movement units and kinect device - Pei-Jam Chen; Yi-Chun Du; Cheng-Bang Shih; Li-Cheng Yang; Hui-Ting Lin; Shih-Chen Fan (2016 International Conference on Advanced Materials for Science and Engineering (ICAMSE), 2016)
It has become an increasingly important issue with respect to improve the efficacy of rehabilitation and increase patient willingness to attend rehabilitation treatment in recent years. Virtual Reality (VR) has been used in combination with medical treatment and technology. More specifically, its skeletal tracking system is being widely used in the field of medicine and rehabilitation. Although the Microsoft Kinect device with low cost and easy development it may encounter the problem of misdetection when it comes to extremity angles or overlapping extremity. In this study, we proposed a new Rehabilitation Gaming System (RGS) which focuses on the upper part of the body with wireless Inertial Measurement Units (IMUs) and Kinect device. The Kinect is being used as the base tracking system by the operation of gaming system. Meanwhile, multiple sets of IMU were integrated into the extremity of the subject to calculate the angles through algorithms. Wireless IMUs could compensate the calculating error of angles in Kinect device. In view of the evaluation of angle difference between the IMUs and Kinect device in different upper extremity gestures when playing the rehabilitation game, the results showed that Kinect has a greater error ratio 23% on extremity angles with regard to depth or overlapping extremities, but calculation by IMUs has higher accuracy and stability. The proposed system has incredible potential to enhance the reliability and validity of the efficacy of rehabilitation.